2008
DOI: 10.1111/j.1365-3024.2008.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation enhances the protective response to Toxocara canis larvae in mice

Abstract: The effect of oral and intraperitoneal supply of sodium selenite on the immune response to, and the course of T. canis larvae infection in mice were determined. The number of worms in the host tissue was reduced but the migratory route of larvae was not affected. Selenite (Se) supplementation influences Se retention in the liver, enhanced IL-5 and eosinophil responses and evoked IL-6 production in mice infected with T. canis. The enhanced protection in mice given Se intraperitoneally was associated with high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…In contrast, the increase of IL‐12 mRNA that was observed in mice supplemented with S. boulardii suggesting that this probiotic blocks the inhibitory effect of T. canis on IL‐12 and participates in the protection against infection. This result is consistent with other researches, who found that an increase in IL‐12, TNF‐α and IFN‐γ may enhance the protective host response against T. canis . In other helminthosis such as Schistosoma mansoni, Trichinella spiralis and Trichuris suis infection, the importance of IL‐12 for the development of a protective immune response was also demonstrated .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the increase of IL‐12 mRNA that was observed in mice supplemented with S. boulardii suggesting that this probiotic blocks the inhibitory effect of T. canis on IL‐12 and participates in the protection against infection. This result is consistent with other researches, who found that an increase in IL‐12, TNF‐α and IFN‐γ may enhance the protective host response against T. canis . In other helminthosis such as Schistosoma mansoni, Trichinella spiralis and Trichuris suis infection, the importance of IL‐12 for the development of a protective immune response was also demonstrated .…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of Se in the host antioxidative response to parasite infections has been reported for Trypanosoma crici (Gomez et al 2002), Toxocara canis (Pilarczyk et al 2008), and Heligmosomoides polygyrus (Smith et al 2005) in mice. The results of Se application differed depending on the infection course and the parasite model used.…”
Section: Introductionmentioning
confidence: 95%
“…Importantly, route of Se treatment (e.g. intraperitoneal injection vs oral ingestion) can affect antiparasite immune responses (Pilarczyk et al, 2008), adding another factor to consider in the use of Se supplementation for prevention or treatment of parasitic infections.…”
Section: Selenium and Intestinal Parasitesmentioning
confidence: 99%